EPLANopt optimization model based on EnergyPLAN applied at regional level: the future competition on excess electricity production from renewables - Prina, Matteo Giacomo; Moser, David; Vaccaro, Roberto; Sparber, Wolfram (International Journal of Sustainable Energy Planning and Management, 2020)
To face environmental and energy security issues, planning an energy system with high penetration of renewables is becoming increasingly important. The EPLANopt model couples a multi-objective evolutionary algorithm to EnergyPLAN simulation software to study the future best energy mix. In this study, EPLANopt is applied to the case study of Niederösterreich, an Austrian region, to inspect the best configurations of the energy system at 2050. This model is used to inspect the competition between different renewable energy integration options. Storage systems, power to gas, power to heat or power to mobility are all integration options taken into account to study their competition in presence of electricity excess from renewables. The results show that in order to decarbonize the energy system the increase of the installed power of renewables is not enough to reach the CO2 reduction objective. Integration methods like the already mentioned storage systems, power to gas, power to heat or power to mobility become relevant. In particular the results show a deep energy efficiency refurbishment coupled to power to heat through heat pumps. Power to gas presents a relevant role in the integration of the excess of electricity from renewables. However, at the increase of electric mobility penetration the available excess of electricity is reduced and the deployment of power to gas decreases.